Sex-specific distribution and classification of Wolbachia infections and mitochondrial DNA haplogroups in Aedes albopictus from the Indo-Pacific. - Qiong Yang; Jessica Chung; Katie L Robinson; Thomas L Schmidt; Perran A Ross; Jiaxin Liang; Ary A Hoffmann (Public Library of Science (PLoS), 2022)
The arbovirus vector Aedes albopictus (Asian tiger mosquito) is common throughout the Indo-Pacific region, where most global dengue transmission occurs. We analysed population genomic data and tested for cryptic species in 160 Ae. albopictus sampled from 16 locations across this region. We found no evidence of cryptic Ae. albopictus but found multiple intraspecific COI haplotypes partitioned into groups representing three Asian lineages: East Asia, Southeast Asia and Indonesia. Papua New Guinea (PNG), Vanuatu and Christmas Island shared recent coancestry, and Indonesia and Timor-Leste were likely invaded from East Asia. We used a machine learning trained on morphologically sexed samples to classify sexes using multiple genetic features and then characterized the wAlbA and wAlbB Wolbachia infections in 664 other samples. The wAlbA and wAlbB infections as detected by qPCR showed markedly different patterns in the sexes. For females, most populations had a very high double infection incidence, with 67% being the lowest value (from Timor-Leste). For males, the incidence of double infections ranged from 100% (PNG) to 0% (Vanuatu). Only 6 females were infected solely by the wAlbA infection, while rare uninfected mosquitoes were found in both sexes. The wAlbA and wAlbB densities varied significantly among populations. For mosquitoes from Torres Strait and Vietnam, the wAlbB density was similar in single-infected and superinfected (wAlbA and wAlbB) mosquitoes. There was a positive association between wAlbA and wAlbB infection densities in superinfected Ae. albopictus. Our findings provide no evidence of cryptic species of Ae. albopictus in the region and suggest site-specific factors influencing the incidence of Wolbachia infections and their densities. We also demonstrate the usefulness of ddRAD tag depths as sex-specific mosquito markers. The results provide baseline data for the exploitation of Wolbachia-induced cytoplasmic incompatibility (CI) in dengue control.